1983
DOI: 10.1007/bf01324959
|View full text |Cite
|
Sign up to set email alerts
|

Gastric heterotopia in rectum complicated by rectovesical fistula

Abstract: Heterotopic gastric mucosa in the rectum produced a rare complication of rectovesical fistula. Diagnosis was made by direct biopsy and 99mTc scanning. Excision of ectopic gastric mucosa, diverting colostomy, and repair did not result in closure of the fistula. Endorectal pull-through constituted definitive treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…[1418] It also can cause failure to thrive because of the chronic abdominal pain associated with recurrent episodes of vomiting and diarrhea. [19] Our case was unique in that the lesion appeared as a giant polyp composed of heterotopic gastric mucosa in the small intestine.…”
Section: Discussionmentioning
confidence: 99%
“…[1418] It also can cause failure to thrive because of the chronic abdominal pain associated with recurrent episodes of vomiting and diarrhea. [19] Our case was unique in that the lesion appeared as a giant polyp composed of heterotopic gastric mucosa in the small intestine.…”
Section: Discussionmentioning
confidence: 99%
“…Reports on the presence of H. pylori in gastric heterotopia in the rectum support the opinion that these bacteria may pass along the whole length of the gastrointestinal tract in a viable form and that the fecal-oral route of transmission is possible [1,2]. The inflammation associated with this infection may contribute to ulceration and bleeding or to more serious complications that are sometimes observed, such as perforation of the bowel, fistula formation or severe hemorrhage [2,6,17,18]. Dye et al [1] reported the resolution of chronic active inflammation of heterotopic mucosa after eradication of H. pylori.…”
Section: Discussionmentioning
confidence: 93%
“…Ectopic gastric mucosa, initially described by Shmidt in 1805, has been found in the esophagus; but it has also been described in other sites of the gastrointestinal tract, such as the tongue [4], the duodenum [5], the jejunum, the gallbladder [6], and the rectum [7]. In the esophagus, it is most commonly located just below the upper esophageal sphincter [2].…”
Section: Discussionmentioning
confidence: 97%
“…Ectopic gastric mucosas have been associated with fistulas: tracheoesophageal fistulas in the case of esophageal EGM, considered by some authors as a perforated peptic ulcer in the EGM [9], and rectovesical fistulas when it comes to EGM in the rectum [7]. …”
Section: Discussionmentioning
confidence: 99%